1998
DOI: 10.1056/nejm199810293391801
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Antiretroviral Therapies in HIV-Infected Subjects with Undetectable Plasma HIV RNA after Triple-Drug Therapy

Abstract: The suppression of plasma HIV RNA after six months of treatment with indinavir, zidovudine, and lamivudine is better sustained by the continuation of these three drugs than by maintenance therapy with either indinavir alone or zidovudine and lamivudine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
98
3
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 289 publications
(108 citation statements)
references
References 24 publications
5
98
3
2
Order By: Relevance
“…PBMCs were collected from 14 patients who participated in AIDS Clinical Trial Group (ACTG) study 343 and who rolled over to ACTG study 5025 after a median of 89 weeks. The details of these studies and the demographics of the study populations have been published elsewhere (17,18 ). Patients in ACTG 343 were antiretroviral naive or had minimal experience with AZT and received a combination of AZT, 3TC, and IDV.…”
Section: Materials and Methods Patientsmentioning
confidence: 99%
“…PBMCs were collected from 14 patients who participated in AIDS Clinical Trial Group (ACTG) study 343 and who rolled over to ACTG study 5025 after a median of 89 weeks. The details of these studies and the demographics of the study populations have been published elsewhere (17,18 ). Patients in ACTG 343 were antiretroviral naive or had minimal experience with AZT and received a combination of AZT, 3TC, and IDV.…”
Section: Materials and Methods Patientsmentioning
confidence: 99%
“…Various randomized clinical trials (24)(25)(26)(27)(28)(29), have shown that 60%-90% of patients treated with HAART achieved sustained suppression of viral load below the detection limit of standard assays.…”
mentioning
confidence: 99%
“…One of the implicit hopes accompanying strategies designed to suppress viral activity is that, at some point, the host's immune system might be able to maintain this suppression either in the absence of, or at least after a de-intensification of, the current medications (8)(9)(10)(11)(12). Unfortunately, with the exception of occasional anecdotal reports of sustained suppression, fairly prompt virologic relapse after discontinuation of HAART has been the predominant pattern observed thus far (13)(14)(15)(16).…”
mentioning
confidence: 99%